Molecular dynamics simulation of the high-temperature pyrolysis of methylcyclohexane. (1st April 2018) - Liu, Yalan; Ding, Junxia; Han, Ke-Li
Abstract: To better understand the initiation and intermediate reaction mechanisms associated with the high-temperature pyrolysis of methylcyclohexane (MCH), the dissociation of MCH is investigated using reactive molecular dynamics (RMD) and density functional theory (DFT) calculations. It is observed that the pyrolysis of MCH is initiated by four types of reaction channels. The initiation of the decomposition is mainly through the CC bond homolysis of the six-membered ring, leading to ring opening and the formation of C7 H14 diradicals. Subsequently, the biradicals undergo successive decomposition by the β-scission of the CC bonds to form ethylene. Furthermore, to provide a detailed description of the pyrolysis behavior of MCH, the distributions of key products, intermediate reactions and corresponding kinetic behavior are systematically analyzed at the atomic level. The apparent activation energy extracted from the RMD simulations is 263.60 kJ/mol at temperatures from 2300 K to 3100 K, which is reasonably consistent with the experimental results.